مركز الأطفال مجهولي النسب في القانون الجزائري - ربعي, كاتية يسرى (جامعة الوادي - university of Eloued, 2017)
يعاني الأطفال المحرومون من كنف العائلة وغياب دورها في الحفاظ على سلامتهم وضمان حقوقهم من انتهاكات عديدة ، ويأتي في مقدمة هؤلاء فئة الأطفال مجهولي النسب التي أصبحت تعرف انتشارا كبيرا في الآونة الأخيرة وهذا راجع حسب الباحثين في علم الاجتماع إلى تدني الوازع الديني والأخلاقي في العديد من مجتمعاتنا. وقد أولت الدول المغاربية من منطلقاتها الإسلامية اهتماما بالغا بالطفل عموما وبهذه الفئة خصوصا ،وتعتبر الجزائر نموذجا واضحا في ضمان حقوق الطفل مهما كانت صفته، سواء من خلال معظم الاتفاقيات الدولية التي تبرمها حول الموضوع أو من خلال القوانين الداخلية التي تسعى من خلالها إلى إفراغ محتوى تلك الاتفاقيات والتجسيد الفعلي لتلك الحقوق. The category does not represent any risk but they get violated and exploited in many societies, especially if we take a sample of children deprived of their family and with the absence of its role in preserving the safety of their children and ensuring their rights, such as children of unknown descent who are increasing in recent times, and according to researchers in sociology this is refered to the low of religious morals in many of our societies. The Maghreb countries in general with its Islamic nature had paid a great attention to the children. Algeria is considered as an active model in ensuring the rights of the child no matter his descent, through most of the international conventions and agreements in this subject or through internal laws that seek to empty the content of the conventions and make those rights effective and practical.
مقال. المجلة الدولية للبحوث القانونية والسياسية . مج1. ع.2. جامعة الوادي
Keywords: حقوق الطفل، الاتفاقيات الدولية، الطفل مجهول النسب،القانون الجزائري.; The chiled rights, international conventions , the child no matter,Algerien laws.